Analysis of the cement industries of Bangladesh in respect to Premier Cement Mills Ltd. - Nigar, Sabrina (BRAC University, 2011)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2010.